The integration of pedagogical games in the teaching process learning: resource to the acquisition in the oral language of students in the initial series / A integração dos jogos pedagógicos no processo de ensino aprendizagem: recurso à aquisição na linguagem oral dos alunos nas séries iniciais - Carmem Simone do Nascimento Araújo (Universidade Estadual de Alagoas, 2019)
: The present research aims to inform how pedagogical games contribute to the intellectual development of students in the 10 and 20 year, through its applicability in the teaching-learning process. The relevant point of the research is characterized in the play as a facilitator in oral language, becoming a fundamental resource for educators in the teaching-learning of children's education. This research is justified by the need to insert playfulness in pedagogical practice and its benefits from elementary education